The effect of Serratia marcescens protease on human lymphocytes transformation - Mahdi, Raghd; Hasan, Shahla; Hasan, Jinan (Iraqi Journal of Science, 2023)
Fifteen blood samples were collected from healthy males and females (6 males &9 females), average age (21-34 years) in heparinized sterile tubes. The extracellularprotease was extracted from a clinical isolate of Serratia marcescens that wasisolated from a patient suffering from urinary tract infection taken from the CentralHealth Laboratory. The extracted protease was purified partial by two steps,precipitation with 30-55% saturation of ammonium sulfate following with dialysisand ion exchange chromatography DEAE-cellulose. The protease concentration was0.15 mg/ml. Two concentration 0.258g/ml and 0.58/ml of protease were preparedand applied in current study. Lymphocyte transformation test using whole blood wasused in order to study the effect of protease concentrations on human lymphocytetransformation. The results show that these were highly significant differences (P <0.05) between control samples and lymphocytes stimulating withPhytohemagglutinin (PHA) and between control sample and 0.58g/ml protease,;while there was no significant differences (P < 0.05) between control sample and0.25 8g/ml protease concentration . That is mean that the higher concentrations ofprotease have the same effect of PHA on human lymphocyte transformation and it isbetter in effect on human lymphocyte transformation than the lowest concentration.